A comparison of wintering in drylot with wintering on bluestem pasture for yearling steers on a wintering, grazing, and fattening program - Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Twenty head of yearling Hereford steers, grading about high good on the basis of USDA feeder grades, were used in the test. They came from near Fort Davis and Paducab, Texas, and were allotted into tow lots on the basis of origin and weight. They were in the heavy end of the calves purchased in the fall of 1958 and were about one year old when started on the test. The only difference in treatment of the two lots was during the winter period.
Keywords: Beef; Drylot; Bluestem pasture; Steers